A transnational history of radio listening groups II: Canada, Australia and the world. Issue 4 (1st October 2016) - Goodman, David
Abstract : The article offers a comparative and transnational history of the organised radio listening group in Canada and Australia, from the 1930s to the 1960s. It compares this history to the earlier development of listening group practice in the UK and US, and examines the export from the 1950s of the Canadian and Australian models of listening group organisation to the developing world. As in the UK and US, listening groups in Canada and Australia were supposed to help combat broadcast propaganda, to encourage a more tolerant and worldly perspective in listeners and to foster skills in articulating and defending personal opinions on public affairs. In addition, however, the Canadian and Australian versions encouraged listener citizens to practice the skills of making collective decisions and undertaking practical projects of community improvement. The metropolitan radio histories of the UK and US have often dominated the field, but in this case the view from Canada and Australia generates a different chronology and different interpretive understanding of the history of the radio listening group.